2009
DOI: 10.1007/s00210-009-0429-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity of isopulegol on experimentally induced gastric lesions in mice: investigation of possible mechanisms of action

Abstract: The present study investigated whether isopulegol, a monoterpene present in essential oils of several aromatic plants, would be able to promote some gastroprotective effect and also verified the possible mechanisms involved in this action. For this study, ethanol- and indomethacin-induced gastric ulcer models in mice and histopathological assessment were used. The roles of NO, sulfhydryls (glutathione, GSH), ATP-sensitive K(+) channels (K(ATP) channels), and prostaglandins were also investigated. Isopulegol ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 61 publications
3
38
0
3
Order By: Relevance
“…22,23) In the present study, a single oral administration of ethanol was found to cause acute gastric bleeding and hemorrhagic lesions in the rat stomach, confirming the detrimental effect of ethanol on the gastric mucosa. Manassantin A pretreatment markedly attenuated this gastric injury, however, suggesting that manassantin A protects against ethanol-induced gastric mucosal injury.…”
Section: Discussionsupporting
confidence: 79%
“…22,23) In the present study, a single oral administration of ethanol was found to cause acute gastric bleeding and hemorrhagic lesions in the rat stomach, confirming the detrimental effect of ethanol on the gastric mucosa. Manassantin A pretreatment markedly attenuated this gastric injury, however, suggesting that manassantin A protects against ethanol-induced gastric mucosal injury.…”
Section: Discussionsupporting
confidence: 79%
“…Brazil not only has one of the world's highest levels of biodiversity but also it has a wealth of traditional knowledge accumulated by local people who have direct access to nature and to the products of biodiversity (Albuquerque et al, 2007). In this sense, information from Brazilian ethnic groups on traditional medicine have contributed to the discovery of pharmacological activities from several plant-derived agents, which have resulted in a signifi cant body of publications (Almeida et al, 2001;Sousa et al, 2004a;2005;De Sousa et al, 2006;Amaral et al, 2007;Silva et al, 2007;Volpato et al, 2008;Silva et al, 2009a;Silva et al 2009b;Morais at al., 2010). In spite of this, the current knowledge on the biodiversity of ecosystems as, for example, of the northeast region, is still very embryonic.…”
Section: Introductionmentioning
confidence: 99%
“…Many other spices/herbs and plant extracts protect against experimentally-induced gastric mucosal injuries through their potential antioxidative effect. These include ginger rhizome, carotenoid and astaxanthin esters, Cissus sicyoides extract, isopulegol and the herb collection Korniozil (1, 57,58,62,63), respectively. Through the interaction with endogenous PG and antioxidative properties, isopulegol, monoterpene a constituent of essential oils of several aromatic plants, induce significant gastroprotection.…”
Section: Herbs and Antioxidantsmentioning
confidence: 99%
“…For instance, Hyptis spicigera essential oil major constituents, monoterpenes, enhances PGE2-induced gastric mucus and reduces ulcer size in addition to increasing COX-2 and EGF expression in gastric mucosa and acceleration of ulcer healing (86). Other spices and plant extracts involved in activation of PG synthesis and healing of gastric mucosal injuries include Boswellic acid, isopulegol, Teucrium polium (3,62,87). Endogenous PG and PGEP1 receptors play a key role in the adaptive protection (88).…”
Section: Herbs-pg Interactionmentioning
confidence: 99%
See 1 more Smart Citation